2021
DOI: 10.4274/tybd.galenos.2019.55477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microorganisms and Antibiotic Resistance Profile Isolated in Intensive Care Unit Patients

Abstract: Objective: Proper surveillance administered by infection control committee members may reduce infection rates and antibiotic use in intensive care units. This study aimed to evaluate the results of blood, respiratory and urine cultures and their changes over the years. Materials and Methods: Among 21632 cultures taken from patients between January 2017 and December 2018, 953 cultures diagnosed with healthcare-related infections constituted the study cohort. SPSS program and incidence formula were used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…As the duration of ICU stay increases, the risk of infection increases and, in turn, infection significantly increases the duration of hospital stay (11 -16). In a study by Aygen et al, the risk of HAIs increased as the duration of hospital stay in nosocomial infections increased (5) (21). In the present study, the pathogens that grew in the samples from the lower respiratory tract were Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 47%
“…As the duration of ICU stay increases, the risk of infection increases and, in turn, infection significantly increases the duration of hospital stay (11 -16). In a study by Aygen et al, the risk of HAIs increased as the duration of hospital stay in nosocomial infections increased (5) (21). In the present study, the pathogens that grew in the samples from the lower respiratory tract were Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 47%
“…In studies conducted in our country, HAI density varies between 15.4 and 44.7 (10). Cetin et al (11) found the HAI density of 21.9 in their two-year analysis of patients hospitalized in the ICU. In our study, we found the HAI density as 17.45.…”
Section: Discussionmentioning
confidence: 96%
“…HAI rates with Gram-negative bacteria, which do not cause infection in healthy individuals but are frequently encountered in ICUs, have increased in recent years (3,8,9,11) (10). In a multicenter study, culture results were examined, and Gram (-) microorganisms were detected with 70.7% (Klebsiella spp., E. coli, Pseudomonas and Acinetobacter, respectively).…”
Section: Discussionmentioning
confidence: 99%